The Impact of Agricultural Technology Adoption on Farming Practices: A Field Survey of Farmers in Pambegua, Kubau LGA, Kaduna State (International Journal of Agricultural Extension and Education, 2025)
This study examined the Impact of Agricultural  TechnologyAdoption on Farming Practices: A Field Survey of Farmers in Pambegua, Kubau LGA, Kaduna State. A field survey  design was employed, targeting 40 purposively selected smallholder farmers actively  engaged in crop production. Data were collected using structured questionnaires  and interviews, and analyzed through descriptive statistics, supported by chi-square  tests to establish associations. Findings revealed that male farmers (70%) dominated agricultural activities, with the  majority being within the productive age range of 31–50 years. Education played a  key role, as farmers with secondary education (35%) demonstrated greater awareness  of agricultural technologies. Exposure to technologies was mainly through mobile  phones (37.5%) and radio/TV programs (25%), while advanced digital platforms  remained underutilized. Adoption levels were highest for improved seeds (35%) and  fertilizers/pesticides (30%), but relatively low for mechanization (20%) and irrigation  (15%). Major constraints identified included high costs of inputs and devices (35%),  poor infrastructure such as network and electricity (25%), lack of training (20%), and  limited access to credit (20%). Farmers suggested training and capacity building (30%),  provision of subsidies (25%), improved extension services (25%), and affordable loans  (20%) as strategies to enhance adoption. The study concludes that while smallholder farmers in Pambegua are receptive to  input-based technologies, structural and financial barriers hinder wider adoption.  Strengthened extension services, policy-driven subsidies, and targeted training are  recommended to bridge the gap between technology availability and farmer utilization.
Keywords: Agricultural technology, adoption, smallholder farmers, constraints, Pambegua, Nigeria